KARAKTERISTIK MOTIVASI DAN SOSIAL RELIGIUS WISATAWAN MELUKAT DI PURA MENGENING, KABUPATEN GIANYAR, BALI - I Ketut Arta Widana (UHN IGB Sugriwa Denpasar, 2023)
Spiritual tourists who come to visit the Mengening Temple and perform the melukat ritual have various characteristics from various perspectives. From a motivational perspective, spiritual tourists can be divided into five according to Abraham Maslow's Theory of Motivation. A tourist in carrying out his tourism activities can have the motivation to meet physical needs, security needs, affection needs, self-esteem needs, and self-actualization needs. In the latest development, Maslow identified other needs after self-actualization, namely transcendental needs. This need is closely related to the motive of melukat spiritual tourism activity. This study found that tourists who perform the melukat ritual at the Mengening Temple have various motives, and most of the tourists' motives are self-actualization and transcendental needs motives. Some tourists stated that there was a security motive for their ritual as they believe in black magic practiced by some people in some countries. From the perspective of socio-religious, spiritual tourists could be part of organied religion, seculer, or even atheist, meaning that spiritual seekers are not restricted by the boundaries of religion or belief